Germantown Boys' Club - Philadelphia Record (1937-1946)
Portrays activities at the Germantown Boys' Club. Depicts boys playing soccer and baseball, playing music, and making crafts. Shows children with animals, a little sister contest, and a Tom Thumb wedding. Highlights the safety patrol and patrol drills. Also includes a lesson in telegraph operation.
These subject entries for the Philadelphia Record newspaper's photo morgue are primarily for Places (buildings, parks, streets, etc.), Things (Bicycles, Bison, Blind Persons [just sampling the B's]), Events (Democratic National Convention 1936, Flourtown Fair, Harvest Week) and Social Constructs (Home Economics, City Planning, Eating & Drinking, etc.). Each of these subjects became a MARC record which included a call number. In the case of these records, the call numbers are the actual folder numbers for the materials referenced. Therefore, these subject headings are really also an index for this section of the Philadelphia Record newspaper's photograph morgue. [The name section of the Philadelphia Record photo morgue represents individuals, A-Z, and
Part of the Philadelphia Record Photograph Morgue Collection; for general information, see collection record.
Gift of the Philadelphia Record
Keywords: Germantown Boys' Club (Philadelphia, Pa.); Soccer -- Pennsylvania -- Philadelphia; Telegraph; Children & animals; Children playing adults -- Pennsylvania -- Philadelphia; School safety patrols -- Pennsylvania -- Philadelphia; Children playing musical instruments -- Pennsylvania -- Philadelphia